2014
DOI: 10.1002/2013je004502
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tides during the 2001 Martian global‐scale dust storm

Abstract: Using observations from the Thermal Emission Spectrometer onboard the Mars Global Surveyor spacecraft and MarsWRF general circulation model simulations, we examine the changes to thermal tides and planetary waves caused by the storm. We find that the extratropical diurnal migrating tide is dramatically enhanced during the storm, particularly in the southern hemisphere, reaching amplitudes of more than 20 K. The tropical diurnal migrating tide is weakened to almost undetectable levels. The diurnal Kelvin waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 51 publications
4
54
2
Order By: Relevance
“…The air mass remains physically intact and circulates around the pole every sol at its fixed local time. This effect is related to the strong diurnal tide in the south polar lower atmosphere that was also observed during the Mars Year 25 GDE (Guzewich et al, ).…”
Section: Resultsmentioning
confidence: 76%
“…The air mass remains physically intact and circulates around the pole every sol at its fixed local time. This effect is related to the strong diurnal tide in the south polar lower atmosphere that was also observed during the Mars Year 25 GDE (Guzewich et al, ).…”
Section: Resultsmentioning
confidence: 76%
“…The opacities of atmospheric dust were based on Mars Global Surveyor Thermal Emission Spectrometer (TES) dust climatology (limb values averaged over ~3 Mars years) as described in Guzewich et al . []. Figure shows that the variation with season of this prescribed dust opacity is in good agreement with the variation of the column optical depth measured by the Mast Camera of MSL (note that the difference in actual magnitude is due to the different wavelengths here).…”
Section: Resultsmentioning
confidence: 99%
“…The modeled data were generated by mesoscale runs, performed with settings otherwise identical to those mentioned in Bridges et al [2014] except that the innermost nest had a resolution of~1.4 km in Gale Crater, in contrast to~4 km used by Bridges et al [2014]. The opacities of atmospheric dust were based on Mars Global Surveyor Thermal Emission Spectrometer (TES) dust climatology (limb values averaged over~3 Mars years) as described in Guzewich et al [2014]. Figure 14 shows that the variation with season of this prescribed dust opacity is in good agreement with the variation of the column optical depth measured by the Mast Camera of MSL (note that the difference in actual magnitude is due to the different wavelengths here).…”
Section: Annual Variation In Vortex Activitymentioning
confidence: 99%
“…Major dust storms are associated with not only a large‐scale increase in dust opacity but also numerous changes in global circulation. Previous studies found pronounced atmospheric responses to major dust storms through intensified Hadley circulation [ Kass et al ., ] and modified thermal tides [ Leovy and Zurek , ; Guzewich et al ., ]. This paper shows that westward traveling wave is one of the signature changes associated with major dust storms.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous studies revealed a close connection between the strength of northern hemisphere eastward traveling waves (especially zonal wave number m = 3) and the occurrence of frontal/flushing dust storms which often led to major dust storms [ Wang et al ., ; Hinson et al ., ]. Previous studies also reported dramatic changes in the Hadley circulation and forced (thermal tides and stationary) waves following major dust storms [ Leovy and Zurek , ; Banfield et al ., ; Guzewich et al ., ; Kass et al ., ].…”
Section: Introductionmentioning
confidence: 99%